Hydrolipidic film and skin elasticity in children and adolescents from Vassouras, Rio de Janeiro: quantitative pilot study (Research, Society and Development, 2021)
Evaluate the FH, the TEWL and skin elasticity in children and adolescents through variables such as skin humidity and oiliness. This is a pilot observational, cross-sectional study of a quantitative nature carried out in a private school in Vassouras, in March 2020, with 27 students between 11 and 15 years. The results demonstrate that a reasonable hydrolipidic balance was found on the face, bad on the neck and a range from reasonable to bad on the upper limbs and from good to bad on the lower limbs. Elasticity wasn’t favorable on the face, neck and most of the upper and lower limbs.  TEWL values varied according to the region and are due to changes in humidity and oiliness, while elasticity underwent changes due to humidity.